Grooming Offences Against Children in Indonesia - Hardiyanti, Devi Tama; Harefa, Beniharmoni; Bakhtiar, Handar Subhandi; Supardi, Supardi (UUM Press, 2023)
The development of information technology has brought about profound changes in people's lives. No aspect of life is left untouched and in the world of crime, especially grooming crimes, which target victims who are children, are also experiencing considerable increase. Legal limitations make it difficult for law enforcement officials to carry out more effective law enforcement. This study examines the legal regime and the factors that encourage crime against children. The present research will be an important point of departure as it will influence the work process of law enforcement officers in terms of child care, especially for child victims. This study uses a legal normative method with a qualitative case study approach, a conceptual approach and a legislative approach. The results show that legal arrangements regarding grooming crimes are regulated using different laws, but do not clearly and explicitly address the many important issues around grooming crimes. As a result, law enforcement officials have difficulty interpreting laws in relation to the relevant causal factors, such as the perpetrator, the victim and social factors.